Characterization of mycobacterial peptidoglycan remodelling enzymes - Mashilo, Poppy (My University, 2018)
Mycobacterium tuberculosis (TB), the causative agent of tuberculosis, is responsible for over one million deaths per annum, a substantive proportion of these due to multidrug resistant or extensively drug resistant strains. The available antibiotics are rapidly becoming ineffective due to the development of resistance mechanisms by the pathogen. Considering this, there is an urgent need for novel and highly effective new TB drugs, with novel modes of action. The peptidogycan (PG) layer in the cell wall has emerged as a rich area for drug discovery. It undergoes constant reconstruction by penicillin binding proteins (PBPs) and other enzymes to allow for cell growth and division, while preventing lysis. In this study, we characterize the function of two Low Molecular Mass PBPs, known as D,D-carboxypeptidases (D,D-CPases, MSMEG_6113 and MSMEG_2433) in Mycobacterium smegmatis, a model organism for TB research. Using a bacterial two hybrid system, we demonstrate that MSMEG_2433 interacts with PonA1 (A High Molecular Mass PBP involved in PG synthesis) and FtsH (An AAA family protease and a member of the divisome complex). We also demonstrate that MSMEG_6113 forms a complex with FtsI (A High Molecular mass PBP and also part of the divisome complex) and a cell division control protein, Cdc48. We demonstrate that the two D,D-CPases associate with their partnering proteins via their C-terminal transpeptidase domain. The importance of these identified interactions for cell division and growth was tested through deletion of partnering proteins from the mycobacterial genome, particularly FtsI and Cdc48. FtsI is essential for mycobacterial growth in vitro as demonstrated by the inability to recover mutants through allelic exchange by homologous recombination, while Cdc48 is dispensable for growth. We noted morphological and cell division defects in the Cdc48 deletion mutant strain. The absence of Cdc48 results in bulging, kinking and chaining phenotypes, in addition to misplacement of the FtsZ ring. Collectively, our observations describe the presence of novel PG hydrolysing protein complexes that may mediate essential steps in PG synthesis and bacterial proliferation. Targeting these complexes may provide an attractive avenue for the development of novel TB therapeutics.
A dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine. May 2018.
Keywords: Mycobacterium tuberculosis